Analysis Of Family Land Disputes Between Heirts Who Still Have Rights And Heirts Who No Longer Have Rights - Zaky Nazera (International Journal of Law and Legal Ethics, 2025)
most people often injustice and fraud when diving inheritance in sibling conflicts. the problem is that heirs who no longer have right but participate in the distribution od inheritance who do  not have their rights. therefore, this problem is resolved through mediation which aims for negotiation supported by a mediator. therefore, disputes and division of heirs land must be resolved through mediation in accordance with applicable regulations. mediation and agreement can be done both inside and outside the court. this study uses descriptive analysis. observing and taking from scientific research john rawls theory of justice is used. the study was conducted in Kp. Tipar Cianjur, west java, because the location is an important dispute in the nuclear family in heritance. the result of the study show that the dispute resolution mechanism carried out by the parties through mediation outside the courts based on mutual agreement is the most common in cases of in heritance divison. in the case, civil laws is used to prioritize  justice, status, and equal right between doughters and sons when divinding inheritance right to inherited land. thus, the islamic law of the parties is not taken into account in this case. to ensure that the distribution of inherited land is carried out evenly, effectively and with full deliberation so that family harmony is careted and each party receives their respective share.